Kualitas Lingkungan Permukiman di Desa Bakau Besar Laut Kec. Sungai Pinyuh Kab. Mempawah - Zairin Zain (Tesa Arsitektur, 2017)
ABSTRACT Settlements in RW 3 and RW 4 in the village of Bakau Besar Laut, District of Sungai Pinyuh is an area adjacent to two small industries; namely shrimp farm and copra processing. Those industries do not have any installation of wastewater treatment plant with the domestic waste polluted settlements, agriculture and farming in the region. This article aims to review the environmental condition in the settlement by conducting tests of the quality of drainage water and drinking water as well as their effects to public health and agriculture. Grab Sampling methods was used for water sampling, questionnaire method was conducted to connect the results of water quality data to the health and agriculture, and statistical method using the Mann Whitney and Anacova used to determine the relationship between the two. The results based on Government Regulation No. 82 / 2001 show that in the radius of 700 m and 1 km is classified into class III and IV with the IR values of 2.50 and 2.63 (high) and the radius of 1.3 km and 1.5 km falls into class I and IV with the IR values of 2.10 and 4.96 (high). These results demonstrate a strong relationship between the quality of housing environment on the level of public health and agriculture showing a correlation of 0.010 and 0.017. It is recommended for this region to have a clean water treatment, to separate waste according to its characteristics and to benefit from the livestock waste for fuel and fertilizer. Keywords : Environmental quality, Settlements, Grab Sampling ABSTRAK Permukiman di RW 3 dan RW 4 Desa Bakau Besar Laut ,Kecamatan Sungai Pinyuh, merupakan kawasan yang berdekatan dengan dua buah industri kecil yaitu tambak udang dan pengolahan kopra yang tidak memiliki IPAL dengan limbah domestik yang mencemari permukiman, pertanian dan peternakan di kawasan tersebut.Tulisan ini bertujuan untuk mengetahui kualitas lingkungan permukiman dengan menguji kualitas air drainase dan air bersih serta pengaruhnya terhadap kesehatan masyarakat dan lahan pertanian. Metode Grab Sampling digunakan untuk pengambilan sample air,metode kuesioner dilakukan untuk menghubungkan hasil data kualitas air terhadap kesehatan dan lahan pertanian.Selanjutnya, metode statistik menggunakan Mann Whitney dan Anakova untuk mengetahui hubungan antara keduanya. Hasil di lapangan dengan mengacu PP 82 tahun 2001 diketahui bahwa pada radius 700 m dan 1 km diklasifikasi ke kelas III dan IV dengan nilai IR 2,50 dan 2,63 (tinggi),sedangkan radius 1,3 km dan 1,5 km masuk kedalam kelas I dan IV dengan nilai IR 2,10 dan 4,96(tinggi). Hasil ini menunjukkan hubungan yang kuat antara kualitas lingkungan permukiman terhadap kesehatan masyarakat dan lahan pertanian dengan hasil didapatkan korelasi sebesar 0,010 dan 0,017. Direkomendasikan untuk kawasan ini memiliki pengolahan air bersih, melakukan pemisahan sampah sesuai dengan karakteristik limbahnya dan memanfaatkan limbah ternak untuk bahan bakar dan pupuk. Kata kunci. Kualitas lingkungan, permukiman, Grab Sampling